Coronary wave energy to predict functional recovery in patients with ischemic left ventricular dysfunction. (3rd October 2022) - Ryan, M; Morgan, H; O'Gallagher, K; Demir, O; Rahman, H; Ellis, H; Dancy, L; Sado, D; Strange, J; Melikian, N; Marber, M; Shah, A; et al.
Abstract: Background: Invasive coronary angiography and non-invasive viability testing are the cornerstones of diagnosing and managing ischemic left ventricular dysfunction. At present there is no single test which serves both needs but, if developed, could revolutionise investigation of this condition. Coronary wave intensity analysis (cWIA) interrogates both contractility and microvascular physiology of the subtended myocardium [1, 2] and therefore has the potential to fulfil this goal. Objectives: We hypothesized that cWIA measured during coronary angiography would predict functional recovery with a similar accuracy to late gadolinium enhanced cardiac magnetic resonance imaging (LGE-CMR). Methods: Patients with a left ventricular ejection fraction ≤40% and extensive coronary disease were enrolled. cWIA, fractional flow reserve and microvascular resistance were assessed with a simultaneous coronary Doppler and pressure-sensing guidewire during cardiac catheterization at rest, during hyperaemia and during low-dose dobutamine stress. Viability was assessed using LGE-CMR. Regional left ventricular function was assessed at baseline and 6-month follow up after optimization of medical therapy +/− revascularization, using transthoracic echocardiography. The primary outcome was regional functional recovery. Results: Forty participants underwent baseline physiology, LGE-CMR and thirty had echocardiography at baseline and 6 months; 21/42 territories demonstrated functional recovery. Resting backward compression wave energy was significantly greater in recovering than non-recovering territories (−5240±3772 vs. −1873±1605 W m –2 s –1, p=0.099, Figure 1), and had comparable diagnostic accuracy to CMR (area under the curve 0.812 vs. 0.757, p=0.649, Figure 2); a threshold of −2500 W mm –2 s –1 had 86% sensitivity and 76% specificity at predicting recovery. Backward expansion wave energy did not predict recovery. FFR was numerically higher in recovering territories (0.81±0.17 vs. 0.71±0.16, p=0.058), whilst hyperaemic microvascular resistance did not differentiate recovering from non-recovering territories (1.97±0.73 vs. 2.29±1.00, p=0.287). The likelihood of functional recovery was similar in revascularised and non-revascularised territories (15/29 vs. 6/13 respectively, p=0.739). Low-dose dobutamine stress increased the energy of all waves, but did not improve the accuracy of cWIA in predicting recovery. In a regression model, resting backward compression wave energy and optimization of medical therapy predicted functional recovery; fractional flow reserve and hyperemic microvascular resistance did not. Conclusions: Backward compression wave energy has similar accuracy to LGE-CMR in the prediction of functional recovery. cWIA has the potential to revolutionise the management of ischaemic left ventricular dysfunction, in a manner analogous to the effect of fractional flow reserve on the management of stable angina. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The British Heart Foundation Clinical Research Training Fellowship